Pengaruh Brand Recognition, Attitude dan confidence Terhadap Minat Beli Konsumen Pada Layanan Online Traveloka (Studi Kasus Pada Mahasiswa Universitas Brawijaya Malang) - Setywan, Meidiangga (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The goal of this research is to examining factors which influence the people’s ineterest on using traveloka online service. This research is using explanatory research model combined with nonprobabilty sampling as a method and insidental sampling for the technique. Moreover,the result of this research processed by Partial Least Square (PLS). Furthermore, the research participated by 120 student of Brawijaya University in Malang who yet using Traveloka online service. The result of this research describes that the interest of using Traveloka online service positively influenced by several variables such as brand recognition, attitude, and confidence. The result also shows that it has two main variables which are attitude that influence the people’s interest of using Traveloka and brand recognition that influence the people’s interest of using Traveloka through attitude. In conclusion, the implications of this research are relevant for Traveloka’s management to focus on and creating marketing strategy based on this research.Keyword: Brand recognition, Atitude, Confidence, Online Service